Prothrombin Complex Concentrates for Coagulopathy in Liver Disease: Single‐Center, Clinical Experience in 105 Patients. Issue 4 (5th February 2019) - Drebes, Anja; de Vos, Marie; Gill, Sunita; Fosbury, Emma; Mallett, Sue; Burroughs, Andy; Agarwal, Banwari; Patch, David; Chowdary, Pratima
Abstract : Patients with liver disease frequently develop coagulopathy, and fresh frozen plasma is traditionally used for correction of coagulopathy to manage and prevent bleeding. Prothrombin complex concentrates (PCCs) offer an attractive alternative because they are more readily available and avoid large‐volume transfusion. This retrospective, single‐center study reviewed clinical use of PCC in patients with acute/chronic liver disease. A total of 105 patients with 194 episodes of PCC administration were reviewed. Data pertaining to indication, dosing, effectiveness, and safety were collected. The effect of PCC on coagulation was analyzed in patients for whom coagulation results were available 7 hours before and after PCC. Data on thromboembolic events and mortality within 4 weeks of PCC administration were captured. Most patients (77%) had chronic liver disease; the remainder had acute liver failure. Indications for PCC were preprocedure prophylaxis and treatment for active/recent bleeding in 48% and 52% of 194 treatment episodes, respectively. The median dose of PCC administered was 22 IU/kg (interquartile range, 16‐29 IU/kg). Before PCC administration, 45% of patients had an international normalized ratio (INR) greater than 2.0, and 36% had fibrinogen levels of at least 1.5 g/L. PCC produced statistically significant reductions in prothrombin time and INR (coadministration with fibrinogen or cryoprecipitate: 3.1 versus 1.9; P < 0.001; no coadministration: 2.3 versus 1.8; P < 0.001). Three patients with multiple risk factors developed thrombotic events (hepatic artery thrombosis, incidental bilateral pulmonary embolism, nonocclusive portal vein thrombosis); there were no cardiovascular or cerebrovascular adverse events. Overall, 46 patients died of causes unrelated to PCC treatment. Conclusion: In patients with liver disease, PCC therapy was effective in improving coagulation test results without an excess of thrombotic events. Further assessment of PCC as hemostatic therapy in this setting is required. Abstract : Prothrombin complex concentrate (PCC) is used increasingly in clinical practice both for the treatment of recent/active bleeding and pre‐procedure prophylaxis in patients with acute or chronic liver disease. Our study reports that PCC therapy is effective in improving coagulation test results, with no evidence of an increased risk of thromboembolism. These findings warrant further studies into PCC as a hemostatic therapy in this setting.